Efektivitas Pelayanan Pembuatan Surat Keterangan Catatan Kepolisian (SKCK) melalui Website Online di Polresta Sidoarjo - Wardany, Anggi Kusuma; Oktariyanda, Trenda Aktiva (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Public service is an activity to fulfill the needs of the community in the form of goods, services, and administrative carried out by public service providers. Realizing how important it is to realize good public service, public service providers are trying to modernize through Electronic Government. E-Government attempted by Polresta Sidoarjo is a Police Record making service presented in the form of a Website. However, in the implementation of Online Police Record application processing, several problems were found, namely the Website was down, the Website features were incomplete, and there was a lack of socialization. From these obstacles, this study aims to describe the effectiveness of the Police Record making service through the Online Website at Polresta Sidoarjo. This type of research is descriptive with a qualitative approach. The focus of this research uses the theory of Website effectiveness according to Suanandar Said, Samsualam, and Andi Surahman Batara (2019) including performance, information, services, and economy. Data collection techniques through observation, interviews, and documentation. The results of the study indicate that the quality of Police Record services through the Online Website at Polresta Sidoarjo has been running effectively although there are still some problems. User experience shows that using the Online Website makes it easier to get a Police Record. However, Polresta Sidoarjo needs to improve the quality of service by adding servers, adding payment methods, providing updated information and new policies related to Police Record, and adding operator officers.